Pengaruh Kualitas SDM dan Disiplin terhadap Kinerja Pegawai dengan Profesionalisme Kerja sebagai Variabel Mediasi dan Faktor Eksternal Sebagai Moderasi: Studi Kasus pada Kantor Kecamatan Kangayan Kabupaten Sumenep - R Tiara Nur Arofah Wajdi; Chamariyah Chamariyah; Subijanto Subijanto (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to examine the effect of Human Resources (HR) quality and discipline on employee performance, with work professionalism as a mediating variable. Additionally, the study considers external factors that may moderate the relationship between these variables, such as technology, leadership style, organizational culture, and work environment. The research uses a quantitative method with an explanatory approach, allowing the researcher to explain the relationships between the involved variables. Data was collected from 41 respondents, who are employees at the Kangayan Subdistrict in Sumenep Regency. The analysis technique used is Partial Least Squares (PLS) to test the relationships between the variables. The results of the analysis show that HR quality and discipline have a significant effect on employee performance, both directly and through work professionalism as a mediating variable. This emphasizes that improving HR quality, which includes employees' knowledge, skills, and abilities, as well as discipline in performing tasks, will enhance overall employee performance. Furthermore, external factors such as technology and organizational culture were found to moderate the relationship between HR quality, discipline, and employee performance. Adequate technology and a supportive organizational culture can strengthen the effectiveness of employee performance by improving professionalism and work discipline. This study provides important implications for the development of HR in the public sector, particularly in terms of planning and implementing policies that can improve HR quality and employee discipline. By enhancing work professionalism and leveraging supporting external factors, government organizations can create a more productive and efficient work environment, ultimately contributing to achieving organizational goals and providing better public services.